2003
DOI: 10.1063/1.1597969
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of microwave dielectric properties and normal vibration modes of xBa(Mg1/3Ta2/3)O3–(1−x)Ba(Mg1/3Nb2/3)O3 ceramics: II. Infrared spectroscopy

Abstract: The relationship between the microwave dielectric properties and the IR active phonons of xBa(Mg1/3Ta2/3)O3–(1−x)Ba(Mg1/3Nb2/3)O3 ceramics was investigated. The IR modes were assigned, and the origin of dielectric response was determined. Among the 15 prominent IR modes, we found that the normal vibrations of the O layers and that of the Ta/Nb layers are strongly correlated to the measured dispersion parameters, such as the resonant strength (4πρ) and the damping coefficient (γ). The frequency shifts of the no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 16 publications
0
28
0
1
Order By: Relevance
“…On one hand, addition of SnO 2 -species reduces the aspect ratio of the grains, which is beneficial to the densification process and is expected to improve the quality factor for the materials. But, on the other hand, the presence of Sn 4+ -ions in the octahedrons will degrade the coherency of the intrinsic lattice vibration modes, which will impose critical effect on the quality factor for the materials [15,16]. Figure 8b shows that, for the 1,350°C/4 h-sintered samples, the quality factor (Qxf) for lightly doped samples (containing 0.05 mol SnO 2 ) is better than undoped ones.…”
Section: Resultsmentioning
confidence: 90%
“…On one hand, addition of SnO 2 -species reduces the aspect ratio of the grains, which is beneficial to the densification process and is expected to improve the quality factor for the materials. But, on the other hand, the presence of Sn 4+ -ions in the octahedrons will degrade the coherency of the intrinsic lattice vibration modes, which will impose critical effect on the quality factor for the materials [15,16]. Figure 8b shows that, for the 1,350°C/4 h-sintered samples, the quality factor (Qxf) for lightly doped samples (containing 0.05 mol SnO 2 ) is better than undoped ones.…”
Section: Resultsmentioning
confidence: 90%
“…Chia et al [23] reported that the oxygen octahedral stretch modes, namely, the A 1g (O) modes at about 780 cm -1 , which represent the 1:1 short-range cation ordering, play an important role on the dielectric properties. Fu et al [24] pointed out that the modes at about 580 cm -1 should be the A 1g modes, which are correlated with the B-O symmetric stretching.…”
Section: Resultsmentioning
confidence: 99%
“…4 indicates that all the spectra profiles are similar to each other, which suggest the same symmetry in accordance with the XRD analyses; however, there is a variation in intensity and position of the polar lattice phonons due to different sintering temperatures. According to the analyses of Ba(Zn 1/3 Ta 2/3 )O 3 reported by Chia et al [23]. and Ba(Mg 1/3 Ta 2/3 )O 3 reported by Tamura et al [28] the modes below 160 cm -1 are related to the vibration between Ba 2?…”
Section: ) 1/3 Nb 2/3 ]O 3 Ceramics and Show That Almost All The Rammentioning
confidence: 94%
“…To correlate the lattice vibrational characteristics of the materials with their dielectric behavior, understanding on the polar vibrational modes in Fourier transformed infrared-red spectra (FTIR) is required. Figure 3 shows how the Sr-incorporation affects the FTIR spectroscopy of the BMT materials, which have recently been assigned [14] and the major resonance peaks are listed in To understand the correlation between the lattice vibrational characteristics of the (1 − x)BMT-xSMT materials with their dielectric properties, the quality factor (Q × f ) and the dielectric constant (K ) of the materials were measured by using a cavity method and are plotted as open and solid symbols in Fig. 4(a), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Since the dielectric properties at microwave frequencies are mainly contributed from the ionic polarization, the study of phonon vibration spectra of Ba(B 1/3 B 2/3 )O 3 has been of particular interest [5][6][7][8][9][10][11][12]. Recently, the Raman phonons [13] and the normal mode for resonant peaks in FTIR spectra [14] in Ba(Mg 1/3 Ta 2/3 )O 3 -Ba(Mg 1/3 Nb 2/3 )O 3 , BMT-BMN, materials were unambiguously identified. The change in microwave dielectric properties of the BMT-BMN materials with the composition has been correlated with the modification on Raman and FTIR spectroscopic characteristics.…”
Section: Introductionmentioning
confidence: 99%